A new and fast cryptographic hash function based on RC4. Issue 6 (1st November 2016) - Yu, Qian; Zhang, Chang N.
ABSTRACT: This article proposes a new cryptographic hash function, called RC4-BHF, which is designed to be both fast and secure. This is a new attempt to design a cryptographic hash function based on the RC4 algorithm. Since vulnerabilities have been discovered in many of the existing hash functions, it is beneficial to construct a hash function which has different internal structure, and RC4-BHF is such a new hash function. Moreover, RC4-BHF is suitable for ultra-low power devices, such as sensor node, which are normally equipped with 8-bit processors, and most other hash functions cannot be implemented efficiently or are not applicable. RC4-BHF can run much faster compared to the existing well-known hash functions and is exceptionally fast on 8-bit processors.